1993
DOI: 10.1002/eji.1830230226
|View full text |Cite
|
Sign up to set email alerts
|

The soluble interleukin‐6 receptor is generated by shedding

Abstract: The ligand-binding subunit (gp80) of the human interleukin-6 receptor (IL-6R) was transiently expressed in COS-7 cells. The metabolically labeled protein was shown to be quantitatively released from the membrane within 20 h. We identified the protein released from the transfected COS-7 cells after purification to homogeneity and N-terminal sequencing as a soluble form of the gp80/IL-6R. Shedding of the gp80 protein was strongly induced by 4 beta-phorbol-12-myristate-13-acetate, indicating that the process was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
259
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 455 publications
(269 citation statements)
references
References 63 publications
8
259
0
2
Order By: Relevance
“…Although many cell surface ligands and receptors, including inflammatory molecules such as TNF-␣, TNFR, and IL-6R (27,28) undergo ectodomain shedding, members of the B7/CD28 costimulatory family have not been identified previously as susceptible to shedding. The TNF superfamily member CD40 is one of the few costimulatory molecules known to undergo ectodomain shedding (29).…”
Section: Icos-inducedmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many cell surface ligands and receptors, including inflammatory molecules such as TNF-␣, TNFR, and IL-6R (27,28) undergo ectodomain shedding, members of the B7/CD28 costimulatory family have not been identified previously as susceptible to shedding. The TNF superfamily member CD40 is one of the few costimulatory molecules known to undergo ectodomain shedding (29).…”
Section: Icos-inducedmentioning
confidence: 99%
“…The TNF superfamily member CD40 is one of the few costimulatory molecules known to undergo ectodomain shedding (29). Ectodomain shedding often is induced in response to receptor/ligand engagement or treatment with phorbol esters (27,28).…”
Section: Icos-inducedmentioning
confidence: 99%
“…Soluble receptors for IL-4, IL-7 and granulocyte macrophage colony stimulating factor (GM-CSF) are translated from differentially spliced mRNAs [l S-201 whereas the soluble receptors for IL-l, tumor necrosis factor (TNT;), and nerve growth factor (NGF) are produced by limited proteolysis of the membranebound receptors (_21,22]. We have recently shown that a soluble form of the IL-6R is generated by shedding and that this process is regulated by PKC [23,24]. For the soluble form of the IL-6R and for a genetically engineered form of the soluble CNTF receptor it has been shown that in the presence of the ligand they act agonistically on cells expressing the signal transducing receptor subunit gp130 .…”
Section: I~rqd~ctionmentioning
confidence: 99%
“…11 Soluble cytokine receptors and growth factor receptors are present as immunomodulatory molecules in body fluids of humans and mice (reviewed in references 12 and 14). Two major nonexclusive mechanisms are responsible for the generation of soluble cytokine receptors: proteolytic cleavage of transmembrane receptors catalyzed mostly by metalloproteases [15][16][17][18][19] or de novo synthesis of alternatively spliced mRNAs encoding soluble receptor molecules lacking a transmembrane domain. [20][21][22][23][24][25][26][27][28] Soluble cytokine receptors appear to be potent regulators of cytokine activities.…”
Section: Introductionmentioning
confidence: 99%
“…TCR-mediated activation of primary or cloned T cells and stimulation of B cells or macrophages by bacteria or their products was followed by an enhanced release of s␥c. A very potent stimulus, previously shown to enhance the proteolytic shedding of several other cytokine receptors, 15,18,23 is the phorbol ester PMA, demonstrating the critical involvement of PKC-dependent pathways in the process of s␥c release. Importantly and in contrast to other soluble cytokine receptors, the presence of ␥c-dependent cytokines such as IL-2, IL-4, IL-7, IL-9, and IL-15 did not influence s␥c production over wide range of concentrations and in all cell types tested.…”
mentioning
confidence: 98%